Phage Therapy as an Approach to Control Salmonella enterica serotype Enteritidis Infection in Mice - Dallal,Mohammad Mehdi Soltan (2019)
Abstract INTRODUCTION: Salmonella enterica serotype Enteritidis (S. Enteritidis) is a cause of food-borne human illness. Given the prevalence of antibiotic resistance of Salmonella Enteritidis and the lack of antibiotic efficacy in future years, its replacement with other agents is necessary. One of the most useful agents is bacteriophages. METHODS S. Enteritidis was identified using a multiplex polymerase chain reaction assay. The effective bacteriophages were isolated from hospital wastewater samples. The effects of the bacteriophages were evaluated both in vitro and in vivo. RESULTS The phage SE20 belonged to the Podoviridae family, and the genome size was 40 kb. The evaluation of phage SE20 at variable pH ranges showed its susceptibility to pH < 3 and pH > 12. The animal model showed that mice infected with S. Enteritidis developed hepatomegaly and splenomegaly, but did not experience gastrointestinal complications after receiving the bacteriophages. CONCLUSIONS The results of this study suggest that phage SE20 is a promising candidate for controlling salmonellosis caused by Salmonella Enteritidis.